Cytokine profile in cerebrospinal fluid of elderly individuals is modulated by three‐month exercise intervention, in parallel with improvements of physical fitness and cognitive functions: Human neuropathology/etiopathogenesis: Links to brain disease. (7th December 2020) - Ukropcova, Barbara; Tomkova, Maria; Kovanicova, Zuzana; Schon, Martin; Slobodova, Lucia; Straka, Igor; Nemec, Michal; Kosutzka, Zuzana; Matejicka, Peter; Turcani, Peter; Sedliak, Milan; Valkovic, Peter; et al.
Abstract: Background: Physical inactivity accelerates ageing‐associated cognitive decline while regular physical exercise improves neurocognitive health, in parallel with improvements of physical fitness and whole‐body metabolism. However, the knowledge on putative bioactive molecules, mediators of exercise benefits in human brain is still very limited. Our aim was to evaluate effects of the aerobic‐strength training intervention on the spectrum of chemokines/cytokines in the cerebrospinal fluid (CSF) of elderly individuals. Method: The CSF from the subgroup of ten elderly individuals (1M/9F; controls/MCI patients 4/6; age = 65.7 ± 3.9yrs; BMI = 25.8 ± 3.5 kg/m 2 ), who underwent 3‐month supervised aerobic‐strength training (3 × 1 h/week), was obtained by the atraumatic lumbar puncture technique before and after training intervention. Levels of 174 chemokines/cytokines were measured with the aid of the cytokine array (RayBiotech). Body weight and composition (Dual‐energy x‐ray absorptiometry/DEXA), BMI, physical fitness (VO2 max, Rockport walk test) and cognitive functions (Addenbrooke's Cognitive Examination/ACE‐R, Trail making test A/TMT‐A, computerized cognitive test Cogstate) were assessed. Result: Aerobic‐strength training improved aerobic fitness (VO2 max, p = 0.03), cognitive functions (ACE‐R score, p = 0.0033; TMT‐A time score, p = 0.027; Learning/working memory, p = 0.016; Visual learning, p = 0.03) and reduced gynoid fat mass (p = 0.01). Three‐month supervised aerobic‐strength training intervention significantly modulated 5 out of 174 examined cytokines in CSF of the elderly individuals. Levels of 2 cytokines were increased by +11.7% and +11.3%, respectively (both p < 0.05), and another three cytokines displayed reduced levels >5% (p < 0.05 for all) in response to training. All distinctly regulated cytokines have previously been shown to be involved in the regulation of neuroinflammation, blood‐brain‐barrier integrity, and neuroprotection. Conclusion: Supervised 3‐month aerobic‐strength training improved aerobic physical fitness and cognitive functions in the elderly. The distinct modulation of chemokines and cytokines in cerebrospinal fluid in response to training intervention could indicate a role of these bioactive molecules in the exercise‐induced adaptive response in human brain. Funding: APVV 15/0253, VEGA 2/0107/18, SAS‐MOST JRP 2018/10.